Oral Contraceptives and Venous Thromboembolism: Focus on Testing that May Enable Prediction and Assessment of the Risk - Douxfils, Jonathan; Morimont, Laure; Bouvy, Céline (Seminars in Thrombosis and Hemostasis, 2020)
Combined oral contraceptives (COCs) induce several changes in the levels of coagulation factors. The levels of procoagulant factors are often increased, while levels of anticoagulant factors are decreased. Fibrinolysis is also affected, even if the effect seems to be more counterbalanced by opposite regulation of profibrinolytic and antifibrinolytic factors. These effects on hemostasis are more pronounced with third- or fourth-generation COC compared with second-generation COC. Venous thromboembolism (VTE) risk increases when multiple risk factors, including genetic and environmental, are present simultaneously. COC use causes changes in coagulation that modify the prothrombotic state induced by preexisting hemostatic alterations in a supra-additive manner. Therefore, testing appears to be of importance not only before implementing COC but also to monitor any potential thrombogenicity induced by COC therapy. Inherited genetic factors, such as factor V Leiden, G20210A prothrombin mutation, antithrombin, protein C or protein S deficiencies, non-O blood group, as well as CYP2C9*2 and the rs4379368 mutations, have all been identified as genetic predictive risk factors of VTE in women. Nevertheless, the screening of these genetic biomarkers is not capable of assessing the phenotypic expression of the risk. This review will focus on the different options for screening the thrombogenic status in this population. Specific attention will be given to the endogenous thrombin potential-based activated protein C resistance, a test aiming at assessing the thrombogenicity induced by hormonal therapies and inherited or acquired thrombophilia.
Keywords: contraception; venous thromboembolism; predictive; blood; coagulation factors; activated protein C resistance